2020
DOI: 10.2147/ott.s241503
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA MT1JP Suppresses Biological Activities of Breast Cancer Cells in vitro and in vivo by Regulating the miRNA-214/RUNX3 Axis</p>

Abstract: Introduction: The purpose of our research was to evaluate MT1JP in breast cancer. Material and Methods: For clinical purpose, tissues were collected, and a correlation analysis ofMT1JP and miRNA-214 gene expressions was conducted. Using an in vitro study, MDA-MB-231 and MCF-7 cell lines were used as research objects in our research. Colony, flow cytometry, TUNEL, transwell, adhesion and wound healing assay were used to discuss the biological activities of the cells. In an in vivo study, tumor weight and volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Similar findings have been reported in breast cancer cells ( Ouyang [ 57 ]). Importantly, levels of RUNX3 and P21 were noticed to be significantly upregulated, whereas levels of MMP2 and MMP9 were found to be downregulated in MT1JP- overexpressing-Bel-7402 and Huh-7 cancer cells ( Mo [ 58 ]).…”
Section: Interplay Between Lncrnas and Runx1supporting
confidence: 90%
“…Similar findings have been reported in breast cancer cells ( Ouyang [ 57 ]). Importantly, levels of RUNX3 and P21 were noticed to be significantly upregulated, whereas levels of MMP2 and MMP9 were found to be downregulated in MT1JP- overexpressing-Bel-7402 and Huh-7 cancer cells ( Mo [ 58 ]).…”
Section: Interplay Between Lncrnas and Runx1supporting
confidence: 90%
“… 22 LncRNA MT1JP sponges miR-214 to inhibit breast cancer progression. 23 DDX11-AS1 has also been reported to sponge several miRNAs, such as miR-499b-5p, miR-873, and miR-326. 13 , 14 , 19 In our study, we found that DDX11-AS1 was distributed in the cytoplasm of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that lncRNAs participate in the regulation of tumor progression ( 18 – 20 ). In the present study, it was demonstrated that SNHG6 promoted melanoma cell viability, migration and invasion by upregulating RAP2B expression via sponging miR-101-3p.…”
Section: Discussionmentioning
confidence: 99%